Performance at the Directorate General of Politics and PUM, Ministry of Home Affairs - A. Annisa Nurul Ramadhani; H. Muh. Nur Sadik; Muhammad Rusdi (LEGAL BRIEF, 2022)
The purpose of this study is to describe and analyze the performance of employees at the Directorate General of Politics and General Administration of the Ministry of Home Affairs regarding bureaucratic reform in improving employee performance at the Directorate General of Politics and PUM of the Ministry of Home Affairs.'' This research was carried out by the Directorate General of Politics and PUM of the Ministry of Home Affairs. This type of research is qualitative research by analyzing events and facts in the field and matching existing theories with a case study approach. Data collection techniques used are observation, interviews and documentation.” The results of the research that has been done show that; (1) The performance of bureaucratic reform employees at the Directorate General of Politics and PUM of the Ministry of Home Affairs with the bureaucratic reform seen from three areas of change: Organizational Arrangement, Improvement of the Management System, and Management of Human Resources Management System as a whole has gone well. (2) The factor of cooperation between leaders and employees in creating good performance is the key to success in realizing bureaucratic reform''.